Spatial, transcriptomic, and epigenomic analyses link dorsal horn neurons to chronic pain genetic predisposition - Cynthia M. Arokiaraj; Michael J. Leone; Michael Kleyman; Alexander Chamessian; Myung-Chul Noh; BaDoi N. Phan; Bettega C. Lopes; Kelly A. Corrigan; Vijay Kiran Cherupally; Deepika Yeramosu; Michael E. Franusich; Riya Podder; et al. (Cell Reports)
Summary: Key mechanisms underlying chronic pain occur within the dorsal horn. Genome-wide association studies (GWASs) have identified genetic variants predisposed to chronic pain. However, most of these variants lie within regulatory non-coding regions that have not been linked to spinal cord biology. Here, we take a multi-species approach to determine whether chronic pain variants impact the regulatory genomics of dorsal horn neurons. First, we generate a large rhesus macaque single-nucleus RNA sequencing (snRNA-seq) atlas and integrate it with available human and mouse datasets to produce a single unified, species-conserved atlas of neuron subtypes. Cellular-resolution spatial transcriptomics in mouse shows the precise laminar location of these neuron subtypes, consistent with our analysis of neuron-subtype-selective markers in macaque. Using this cross-species framework, we generate a mouse single-nucleus open chromatin atlas of regulatory elements that shows strong and selective relationships between the neuron-subtype-specific chromatin regions and variants from major chronic pain GWASs.